إنشاء موديل رياضي لتحديد أكاسيد النتروجين المنبعثة من نواتج الاحتراق في محركات الاحتراق الداخلي - ديوب محمد (Latakia University Journal -Engineering Sciences Series, 2017)
تركز البحث على استنتاج نموذج رياضي لتحديد نسبة أكاسيد النتروجين المنبعثة عن محركات الاحتراق الداخلي استناداً إلى معادلات التفاعل الكيميائية المباشرة والعكسية للوقود التقليدي مع استخدام للعديد من معاملات التصحيح، بالإضافة إلى إمكانية تطوير هذا النموذج. اعتمد البحث على معرفة تغيرات تراكيز أكاسيد النتروجين الناتجة عن احتراق الوقود في محركات الاحتراق الداخلي التي تعمل على المازوت والبنزين، خلال زمن العمل، ومن ثم تحويل هذه العلاقة لحساب نسبة التراكيز وفقاً لزاوية دوران عمود المرفق في المحرك. تم خلال البحث استنتاج العلاقة بين تراكيز أكاسيد الآزوت الموجودة في الملوثات الغازية وزاوية دوران عمود المرفق، أي: ، من خلال إجراء تحليل رياضي للمعطيات عند نظام عمل محدد للمحرك، واستناداً لذلك تمّ بناء العلاقة بين درجة الحرارة وزاوية الدوران. . تمّ مقارنة النتائج النظرية للموديل مع النتائج المعملية (المخبرية) الخاصة. من أجل اختبار صلاحية ووثوقيه الموديل الرياضي تمت المقارنة مع المخطط الدليلي الفعلي لمحرك ديزل عند زوايا دوران مختلفة لعمود المرفق. كانت القيم الناتجة عن النموذج الرياضي متقاربة مع قيم النتائج المخبرية، حيث لم تتجاوز نسبة الاختلاف بين القيم المخبرية وقيم النموذج الرياضي عن . The research focused on the conclusion of a mathematical model to determine the proportion of nitrogen oxides emitted from the internal combustion engine based on the equations of chemical interaction of direct and reverse the conventional fuel with the use of many of the correction coefficients, as well as the possibility of developing this model. Search to find out the concentration of nitrogen oxides NO changes resulting from the combustion of fuel in internal combustion engines that run on diesel fuel and gasoline adopted, during work time, and then transform this relationship to calculate the ratio of the concentrations according to the angle of rotation of the engine crankshaft. During the search it was concluded the relationship between the concentration of nitrogen oxides in the gaseous pollutants and the angle of rotation of crankshaft, through a mathematical analysis of the data at the specific work of the engine system, and it is based on the construction of the relationship between temperature and angle of rotation, . In order to test the validity and reliability of the model athlete it was compared with the actual hand-made diesel engine planned at different angles of rotation of the shaft attachment. The resulting model sports convergent values with the values of laboratory results, which did not exceed the difference between the laboratory values and the values of the mathematical model for .